The impact of the revised ESC Dyslipidaemia Guidelines on lipid-lowering therapy: simulating the need for PCSK9 inhibition in a contemporary ASCVD cohort. (25th November 2020) - Blaum, C; Brunner, F.J; Kroeger, F; Braetz, J; Bay, B; Graef, A; Gossling, A; Lorenz, T; Zeller, T; Karakas, M; Schnabel, R.B; Westermann, D; et al.
Abstract: Introduction: The recently updated ESC guidelines on the management of dyslipidaemias recommend a more intense LDL-cholesterol (LDL-C) reduction. For patients with atherosclerotic cardiovascular disease (ASCVD) the LDL-C goal has been revised to ≤55 mg/dl with a concomitant class IA upgrade for cost intensive PCSK9 inhibitors. Purpose: We aim to quantify the need for PCSK9 inhibitors to achieve the revised LDL-C target compared to former ESC recommendations in ASCVD patients Methods: We included all patients with ASCVD (angiographically documented coronary artery disease, history of peripheral artery disease or stroke) from an observational cohort study ongoing since 2015. A simulation treatment algorithm adding sequentially a high intensity statin, ezetimibe and a PCSK9 inhibitor in case of a missed treatment target was applied with consideration of both partial and total statin intolerance. The need for PCSK9 inhibitors was calculated for 3 recommendations: 1. LDL-C treatment target ≤55 mg/dl (ESC 2019 Guidelines), 2. LDL-C treatment target ≤70 mg/dl (ESC 2016 Guidelines) and 3. risk-based use of PCSK9 inhibitors restricted to patients with a residual LDL-C >140 mg/dl or >100 mg/dl with clinical/angiographic risk factors (ESC consensus update 2017). Results: We included 1936 patients (mean age 69 years, 74% male). Median LDL-C at inclusion was 86 mg/dl, with 60% of patients taking lipid lowering medication (55% statin only, 4% statin + ezetimibe, 1% ezetimibe only). Table 1 shows the distribution of medications required to meet recommendations 1–3. After simulated stepwise intensification of lipid lowering therapy 99% of patients achieved the revised LDL-C target of ≤55 mg/dl, with a need of 23.5% for a PCSK9 inhibitor. For the former LDL-C target of ≤70 mg/dl the need for PCSK9 inhibitors was 10.5%. Restricting the use of PCSK9 inhibitors to the highest risk patients according to the ESC 2017 consensus statement reduced the need for PCSK9 inhibition to only 1.4% with slightly fewer patients achieving their LDL-C target (78% for ≤55 mg/dl and 91% for ≤70 mg/dl respectively). Conclusion: The revised LDL-C treatment goals substantially increase the projected need for PCSK9 inhibitors with an unclear health economic impact. Identification of ASCVD patients with a reasonable benefit/cost-ratio of PCSK9 inhibition remains to be investigated urgently. Funding Acknowledgement: Type of funding source: None